PENDEKATAN VECTOR ERROR CORRECTION MODEL (VECM) PADA VARIABEL MAKRO EKONOMI TERHADAP INFLASI DI KALIMANTAN TIMUR - Rafdiansyah, Daffa; Sutrisno, Sutrisno; Ellyawati, Noor (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2024)
East Kalimantan province is one of many provinces in Indonesia whose average inflation rate is still below the national inflation target. This study aims to analyze how the influence of short – term and long-term on several macroeconomic variables such as the money supply (M1), interest rates, and the rupiah exchange rate on inflation in East Kalimantan province in the period 2018.1-2022.12. This study uses secondary data with econometric analysis techniques through Vector Error Correction Model (VECM) approach to estimate the short-term and long-term relationship between variables, with several stages of tests such as stationarity test, determination of optimum lag, cointegration test, to the Test Impulse Response Function (IRF) and Variance Decomposition (VD). The results of VECM estimation show that there are three variables with significant effect, plus one variable error correction. The three variables include inflation at a lag of 2, the exchange rate at a lag of 1 and the money supply at a lag of 3. The statistical value of the error correction parameter of 3.22% means that there is a short-term adjustment mechanism to the long term. So in the short term, the money supply and exchange rate have a significant positive influence, only interest rates have no influence. In the long run, the money supply has a significant positive effect, interest rates have a significant negative effect, while exchange rates have no effect on inflation. Keywords:  Exchange Rate,  Inflation,  Interest Rate,  Money Supply,  Vector ErrorCorrecton Model (VECM)